2022
DOI: 10.3390/life12050698
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Association between TNFA Polymorphisms (rs1799964 and rs361525) and Susceptibility to Cancer in Systemic Sclerosis

Abstract: Tumor necrosis factor (TNF)-α is a proinflammatory cytokine that plays an important role in the pathogenesis of autoimmune diseases. The aim of the study was to establish an association between TNF-α promoter variability and systemic sclerosis (SSc). The study included 43 SSc patients and 74 controls. Four single nucleotide polymorphisms (rs361525, rs1800629, rs1799724, and rs1799964) located at the promoter of the TNFA gene were genotyped using commercially available TaqMan allelic discrimination assays with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Furthermore, recent findings indicate that the TNFA C rs1799724 variant is associated with an elevated risk of SSc. Additionally, based on the detection of cancers within their cohort, the authors have speculated that the CT rs1799964 and AG rs361525 genotypes may exacerbate cancer susceptibility in individuals with SSc [129].…”
Section: Tnf Superfamily Member 4 (Tnfsf4)mentioning
confidence: 99%
“…Furthermore, recent findings indicate that the TNFA C rs1799724 variant is associated with an elevated risk of SSc. Additionally, based on the detection of cancers within their cohort, the authors have speculated that the CT rs1799964 and AG rs361525 genotypes may exacerbate cancer susceptibility in individuals with SSc [129].…”
Section: Tnf Superfamily Member 4 (Tnfsf4)mentioning
confidence: 99%
“…Variations located in the promoter region of the TNF-α gene (such as rs1800750 at position −376G/A and rs361525 at position −238G/A) [36,37] are believed to impact the expression of TNF-α and are recognized as functional single-nucleotide polymorphisms (SNPs) [35]. The rs361525 polymorphism has been linked to different hemato-oncologic conditions such as chronic myeloid leukemia (CML) [13]; other types of cancers including breast cancer, lymphoma [37], gastric cancer [38], and lung cancer [39]; and various other medical conditions such as graft versus host disease, ear infections in children, nasal polyps, diabetes, the decline of verbal memory, and sudden infant death syndrome [37], as well as liver cirrhosis [40], psoriasis [41], and systemic sclerosis [42]. The rs1800750 polymorphism has also been investigated in different conditions, like cancer, diabetes, migraine, or multiple sclerosis [36], but to the best of our knowledge, not in CLL.…”
Section: Cytokines In Cllmentioning
confidence: 99%
“…In this collection, Kosałka-Węgiel and colleagues present very interesting results of a genetic association study investigating four single nucleotide polymorphisms (i.e., rs361525, rs1800629, rs1799964, and rs1799724) located within the promoter of the TNFA gene in a SSc cohort compared to a control group [ 7 ]. In this original contribution, the authors found an association between the C rs1799724 allelic variant and an increased risk of SSc.…”
mentioning
confidence: 99%
“…In this original contribution, the authors found an association between the C rs1799724 allelic variant and an increased risk of SSc. In addition, they reported that the CT rs1799964 and AG rs361525 genotypes might enhance cancer susceptibility in SSc patients [ 7 ]. Furthermore, it was found that patients with the AG rs1800629 genotype had a higher prevalence of anti-Ro52, a type of antibodies that have been associated with a higher risk of developing different kinds of cancers, particularly those affecting the digestive and female reproductive systems [ 7 , 8 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation